Reflection on two Ambio papers by P. J. Crutzen on ozone in the upper atmosphere:This article belongs to Ambio’s 50th Anniversary Collection. Theme: Ozone Layer - Nielsen, Ole John; Bilde, Merete (Ambio, 2021)
We here reflect on two important articles on stratospheric ozone depletion written by P. J. Crutzen (1974) and P. J. Crutzen and D. H. Ehhalt (1977) in the early 1970s. These articles provide a clear description of the stratosphere and the most important chemical reactions involved in stratospheric ozone depletion. They present modeling results and provide recommendations for future research on stratospheric ozone depletion caused by chloro-fluoro-carbons, supersonic transport, nitrous oxide, and nuclear explosions. These two articles represent the beginning of a scientific era, which led to discovery of the Antarctic ozone hole and political action in the form of the Montreal Protocol and its amendments.